Avaliação sorológica e molecular da infecção por Toxoplasma gondii em bubalinos da Ilha de Marajó naturalmente infectados - SANTOS, Cássia Maria Pedroso dos (Universidade Federal do Pará, 2017)
In order to analyze the occurrence of Toxoplasma gondii in buffalo Marajó Island by serological and molecular method, blood samples and brain tissue of 100 buffaloes were collected. Blood sera were tested by indirect immunofluorescence assay (IFA) using a 1:64 dilution as the cutoff point for T. gondii, these samples were tested for the presence of antibodies IgG anti-T. gondii. To confirm the presence of T. gondii B1 gene in genomic material of blood and brain tissue samples were subjected to amplification by polymerase chain reaction (nested PCR). Among the tested sera buffaloes, 14 (14%) were reactive against T. gondii by the IFA technique, while blood samples and brain tissue tested 4- (4%) were amplified DNA by the technique of T. gondii PCR, 3 (3%) in blood samples and 1 (1%) in brain tissue samples. Despite the low occurrence of antibodies anti-T. gondii in serum buffalo, it can be concluded that infection by this parasite is present in buffalo breed in Marajo, moreover, it was possible to detect the genomic material of T. gondii in blood samples and brain tissue these animals, thus there is the need for further research, using the molecular technique for the diagnosis of toxoplasmosis since the detection of the bioagent buffaloes becomes even more relevant to the importance of these animals in the epidemiological cycle of toxoplasmosis as possible sources of infection primarily for the human being.